2021
DOI: 10.1177/0267659121995996
|View full text |Cite
|
Sign up to set email alerts
|

Temperature management on cardiopulmonary bypass: Is it standardised across Great Britain and Ireland?

Abstract: Temperature management is an essential element of cardiopulmonary bypass (CPB), as indicated in the Guide to Good Practice in Clinical Perfusion, ‘The safe conduct of CPB requires the clinical perfusionist to measure and control. . . blood temperature. . . during the period of bypass’. To review current practice, we have conducted a research survey into the management of temperature on CPB. Surveys were distributed to each centre in Great Britain and the Republic of Ireland, investigating numerous temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Another important issue is body temperature management.As we all known, wide incision, massive infusion uid and blood in such surgery make maintain body temperature is very di culty. CPB can effectively manage the temperature 19 , to maintain the high temperature of normal value before the downtime of CPB. There are many ways to maintain body temperature in case of hypothermia after CPB, such as using water blanket, warm air heater and infusion heater.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue is body temperature management.As we all known, wide incision, massive infusion uid and blood in such surgery make maintain body temperature is very di culty. CPB can effectively manage the temperature 19 , to maintain the high temperature of normal value before the downtime of CPB. There are many ways to maintain body temperature in case of hypothermia after CPB, such as using water blanket, warm air heater and infusion heater.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the tympanic membrane temperatures are lower than hypothalamic temperatures and can change in opposite directions [19]. Although the arterial outlet temperatures have been shown to correlate well with jugular bulb temperatures, in a survey of cardiac surgeons in the United Kingdom, only 33% rely on the arterial outlet temperature, and thus, it is not universally used [20]. While pulmonary artery catheters and jugular bulb catheters have excellent intra-class correlation (> 90%) and are considered to approximate brain temperatures best, they are invasive catheters and are currently not the standard of care [19].…”
Section: Discussionmentioning
confidence: 99%
“…20 We usually use nasopharyngeal temperature monitoring during cardiac surgery with a double purpose: to have a second estimate of brain temperature (along with that obtained in the arterial branch of the oxygenator) and to monitor the temperature during weaning from CPB. Although nasopharyngeal is possibly the most used temperature probe worldwide in perfusion and is one of the methods recommended by the current guidelines for weaning from CPB and immediate postbypass temperature measurement (recommendation class IIa, level of evidence C), 14,21 only 52% of adult cardiac centers throughout Great Britain and Ireland monitor nasopharyngeal temperatures during CPB; 21 that figure reflects an insufficient degree of monitoring of a parameter that is crucial during cardiovascular surgery. However, despite its popularity, the nasopharyngeal probe may not provide an accurate measurement of brain temperature.…”
Section: Discussionmentioning
confidence: 99%